O naturze sporów kompetencyjnych. Konflikty pomiędzy organami władzy państwowej w polskiej myśli polityczno-prawnej na przełomie XX i XXI wieku - Wojtacki, Maciej (Przegląd Politologiczny, 2018)
Competency disputes between the organs of state authority are one of characteristics of the Polish political system functioning at the turn of the 20th century, that is since regaining independence until today. The first conflicts between the organs of executive and legislative powers emerged in the period of the Second Republic of Poland. More frequently referred to as constitutional disputes then, these competency conflicts were focused around Marshall Józef Pi³sudski, and their main cause was the interpretation of the Small Constitution, and then the Constitution of 17th March 1921. These interpretations were particularly skillfully applied by the supporters of the Marshall, especially by Stanis³aw Car, Minister of Justice, whose name gave rise to the notion of carowanie [bewitching] of the Constitution. The available sources allow the conclusion that competency disputes were one of the causes for amending the Constitution in 1935, at least from a legal point of view. The period of the Second World War also saw disputes that can be called conflicts of competency. This time the representatives of executive power played the main roles. The conflicts between Prime Minister W³adys³aw E. Sikorski and President W³adys³aw Raczkiewicz resulted in the clearly reinforced position of the former. After 1989, competency disputes became a permanent element of political life, as was the case after regaining independence in 1918. Analogous to the interwar period, a problem with the interpretation of the Constitution emerged, in particular after the Small Constitution was passed in October 1992. The notion of the ‘Falandization of law’ was coined in reference to the advisor to President Lech Wa³êsa – Professor Lech Falandysz. Also the 1997 Constitution, which remains in force, was a source of conflicts, this time between President Lech Kaczyñski and Prime Minister Donald Tusk. Competency disputes over the last two decades clearly show the direction of the further evolution of the Polish political system towards strengthening the position of the Prime Minister while limiting the powers of the head of state.